It takes two to Tango: The joint effect of democracy and fiscal capacity on economic growth in Indonesia - Hidsal Jamil; Candra Fajri Ananda; Ferry Prasetyia (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2022)
The literature continues to debate the effects of democracy and fiscal capacity on economic growth, both partially and jointly. To remedy the literature puzzle, this study examines the economic growth effects of democracy and fiscal capacity in 34 Indonesian provinces from 2016 to 2021. Using a fixed-effect model, this study documents no evidence of a partial effect; rather, it finds a joint effect of democracy and fiscal capacity on Indonesian economic growth. These findings remain relatively robust even when provincial heterogeneity, COVID-19 pandemic shocks, and sectoral composition are factored into the model. This finding indicates that regions with democracy and strong fiscal capacity possess relatively fast per capita GRDP growth. Based on these findings, the study concludes that democracy and fiscal capacity should exist side by side. Indonesia's sub-national economic growth strategy, like a tango game, requires reforming two types of decentralization: political decentralization to improve the quality of democracy that upholds the merit system and fiscal decentralization to expand local tax capacity to finance public goods productively.